Analysis of Hydroquinone and Kojic Acid Content in Three Brand Body Lotions Using High Performance Liquid Chromatography - Yessy Dwi Anggraini; Khoirul Anwar; Aqnes Budiarti (Sam Ratulangi University, 2023)
Treatment of hyperpigmentation can be done with several compounds, including a combination of hydroquinone and kojic acid in cosmetic preparations that are considered safe and effective. This study aims to analyze the levels of hydroquinone and kojic acid in three trademarks of body lotion using HPLC. The study used HPLC at a wavelength of 283 nm. The stationary phase used was C18, and the mobile phase was a mixture of acetonitrile:aquabidest (20:80, v/v) with a flow rate of 1.0 mL/min. Validation tests were carried out, including linearity, sensitivity (LOD and LOQ), selectivity, precision, and accuracy. The analytical method was applied to 3 body lotion preparations. The linearity test of hydroquinone and kojic acid with a value of r = 0.999; Hydroquinone LOD 0.274 g/mL; LOQ of hydroquinone 0.913 g/mL; LOD of kojic acid 0.420 g/mL; LOQ of kojic acid 1,401 g/mL; selectivity test 1.5; the precision test of hydroquinone and kojic acid resulted in the value of %RSD 2%; hydroquinone accuracy 99.200-100.450%; kojic acid 99.454-100.450%. The content of hydroquinone body lotion brand A, 0.854%, B 0.470%, and C 1.557%, kojic acid content in body lotion brand A 0.823%, B 0.510%, and C 1.497%. The results showed that all the results of the validation test fulfill the requirements of the validation parameters and the results of the analysis of the content of hydroquinone and kojic acid in the three trademarks of body lotion fulfill the requirements. Keywords: Body lotion; hydroquinone levels; kojic acid